Motivasi Belajar Siswa Pada Pembelajaran Matematika Kelas IV SDIT Al-Hidyah Pekanbaru - ., Clarisa Yahya Yolanda; ., Siti Quratul Ain (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The purpose of this research is to find out how students learn motivation in learning mathematics in class IV SDIT Al-Hidayah Pekanbaru. This type of research is qualitative research with a case study approach. This research was conducted at SDIT Al-Hidayah Pekanbaru with the sample being fourth grade students. Collection techniques used in this study include: interviews, observation and documentation. The data analysis used was Miles and Huberman's qualitative data analysis. Based on the results of the data analysis that has been carried out, student motivation in learning mathematics in class IV SDIT Al-Hidayah Pekanbaru is still somewhat inadequate according to the aspects that have been researched and observed. As for signs such as a lack of student motivation in learning mathematics, namely, there are still many students who are lazy in learning or doing assignments given by the teacher while learning mathematics is in progress, there are still students who do not pay attention to the teacher and instead are engrossed in talking and playing with friends when the teacher is explaining in front of the class, there are still students who lack confidence, such as cheating on their friends and don't want to be ordered to do blackboard assignments, there are still students who are sleepy when learning mathematics is in progress, even though the learning environment is quite good.